Utilization of Microalgae as Carbon Absorbent Material for Environmentally Friendly Concrete in Tropical Coastal Areas - Risjunardi Damanik; Khadijah; Hanifah Sriamelia (CV. Get Press Indonesia, 2026)
This study evaluates the mechanical, durability, and carbon sequestration performance of a 1:1 blend of Chlorella vulgaris and Spirulina platensis biomass as a supplementary cementitious material (SCM) in concrete for tropical coastal infrastructure. Five replacement levels (0%, 3%, 5%, 7%, and 10% by weight of cement) were tested under ambient tropical conditions (28–32°C, 75–85% RH) reflecting West Sumatra's coastal environment. Compressive and flexural strength, water absorption, chloride penetration resistance, and CO₂ sequestration via thermogravimetric analysis were comprehensively assessed. Results indicate that 5% replacement (MA-5) achieved the optimal balance: 28-day compressive strength of 31.4 MPa (6.4% below control), while demonstrating 12.3% improved chloride resistance and a net carbon sequestration rate of 38.7 kg CO₂/m³ of concrete. Scanning electron microscopy confirmed microalgae cell-wall fragments filling interfacial transition zones, reducing porosity by 11.2% and enhancing matrix densification. The findings demonstrate that microalgae-incorporated concrete at 5% OPC replacement is a technically viable, low-carbon alternative for coastal tropical construction, offering both structural adequacy and environmental benefits. Adoption in Indonesia's green building programs is recommended, with future research needed to validate performance at industrial scale and assess long-term durability under field marine exposure.